Meningkatkan Hasil Belajar Fisika Melalui Model Pembelajaran Cooperative Learning Tipe Take And Give Pada Siswa Kelas XI IPA 1 SMA Negeri 3 Bengkalis - - Nurhadi (STAIN Bengkalis, 2018)
This research is a classroom action research (CAR) by using Cooperative Learning (Take and Give) to improve physics learning outcome. The results showed that there is improvement on the student learning outcomes during the implementation of Cooperative Learning Model (Take And Give Type). Thus, based on the results of research indicate that through model learning Cooperative Learning (Take And GiveType) can improve students’ physics learning outcomes class XI IPA 1 SMA Negeri 3 Bengkalis in the year 2012/2013.___________________Keywords: Learning Model, Take and Give Model, Physics Learning Outcome